Pengaruh Green Banking Terhadap Industri Perbankan di Indonesia - Kirani, Prade Setyawati Dyah; Astuti, Ismadiyanti Purwaning (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The problem currently being faced by banks regarding profitability is that it is experiencing a decline due to still recovering after the Covid-19 pandemic that hit from 2019-2021. One way for banks to overcome this problems, green banking can also help banks overcome problems related to envirommental damage. Green banking practices can help the surrounding enviromment to be more protected because it leads to digitalizing and paperless. This research aims to analyze the influence of geen banking on bank profitability in Indonesia for 5 years. Sampling in this study used a purposive sampling technique and 7 banks were obtained that met the criteria. The analysis method used in this research is panel data by testing via Eviews 10. The independent variable variable is green banking with projections (ATM units, paper use, water use) while the dependent variable is bank profitability with ROA projections. The resuts of this research are that ATM units have an effect on ROA, while paper use and water use have nothing to do with ROA. Howefer in simultaneous testing it was found that the implementation of green banking projected in ATM units, paper use, and water use had a positive and significant influence on profitability.